2017
DOI: 10.3389/fcomm.2017.00014
|View full text |Cite
|
Sign up to set email alerts
|

Training of Verbal Working Memory at Sentence Level Fails to Show Transfer

Abstract: During the past decades, working memory (WM) training has attracted considerable research attention, but its transfer to untrained tasks is still controversial. In a randomized controlled trial, we investigated the possible transfer effects of a novel sentence-level WM training regime. Sixty-eight healthy Finnish adults were randomized into either a WM training group or an active control group. The WM training group practiced for 4 weeks with two adaptive sentence-level WM training tasks, namely, a novel sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
5
0
4
Order By: Relevance
“…Practice distribution may influence motivation during the period of training, however, since our participants’ level of motivation increased with massed practice and decreased with spaced practice. Fellman et al [62] also reported a significant decrease in motivation during the training. We speculate that motivation declines over time.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Practice distribution may influence motivation during the period of training, however, since our participants’ level of motivation increased with massed practice and decreased with spaced practice. Fellman et al [62] also reported a significant decrease in motivation during the training. We speculate that motivation declines over time.…”
Section: Discussionmentioning
confidence: 98%
“…Zhao et al [61] found that higher levels of motivation were related to greater training gains, but not to transfer effects. Fellman et al [62] reported that participants’ self-perceived training gains were not substantiated by their actual performance. Given these inconclusive results, it seemed worthwhile to further investigate the link between motivational and self-perception variables on the one hand, and training-related performance on the other.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the sentences were updated with new words, they remained at all times semantically and syntactically plausible. SUS has demonstrated adequate psychometric properties (Fellman et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of correctly recalled words, regardless of the order they were recalled in, was used as the outcome variable. See Fellman et al ( 2017 ) for details.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao, Xu, Fu y Maes (2017) trabajaron con 45 jóvenes divididos en dos grupos (alta y baja motivación) durante catorce días para verificar el efecto de la motivación en la transferencia de ganancias. Para el entrenamiento, usaron tareas La hipótesis planteada por von Bastian y Eschen (2016), en la cual la efectividad del entrenamiento es mayor cuando las tareas son adaptativas, fue contrastada con mediciones hechas a 130 jóvenes Fellman et al (2017) estudiaron los efectos de transferencia en 68 participantes asignados de manera aleatoria a un grupo de entrenamiento y de control activo de atrás N visoespacial en ambos casos, y para valorar la transferencia cercana, tareas atrás N verbales, mientras que para la intermedia una de actualización numérica de estructura diferente, y para la lejana, tareas de control ejecutivo y de razonamiento.…”
Section: Estudios Previos Relacionadosunclassified